Phase formation and dielectric properties of Ba(Zn1/3Nb 2/3)0.75Ti0.25O3 ceramic - P. Ketsuwan (2018)
The Ba(Zn1/3Nb2/3)0.75Ti 0.25O3 ceramic was prepared by a conventional mixed oxide. The thermal analysis (TG-DTA) and x-ray diffraction were used for investigating of phases formation. A pure phase of BaZn1/3Nb2/3O 3 was obtained and revealed microwave dielectric behavior.